Splenic abscess and perisplenic hematoma complicating Osler (Indian Journal of Case Reports, 2018)
A 52-year-old diabetic gentleman was referred to our center with a 3-week history of fever, left-sided abdominal pain, and progressive breathlessness. He also had history of recurrent epistaxis since childhood. Contrast-enhanced computerized tomography chest and abdomen revealed a splenic abscess, left pulmonary arteriovenous malformation, and left pleural effusion. He was managed conservatively with intravenous antibiotics and an antifungal. A repeat imaging was done after 3 weeks which showed resolution of abscess but an increase in the size of the perisplenic hematoma. An ultrasound guided pigtail catheter was inserted into the peri-splenic hematoma and it was drained. He had also developed an acute cerebellar infarct detected on magnetic resonance imaging of brain, which also showed other chronic infarcts of varying age. A diagnostic nasal endoscopy revealed multiple telangiectasias, and Osler